Piloted Ignition of Cylindrical Wildland Fuels Under Irradiation - Lin, Shaorun; Huang, Xinyan; Urban, James; McAllister, Sara; Fernandez-Pello, Carlos (Frontiers in Mechanical Engineering, 2019)
Recent mega wildfires have become one of the most dangerous and devastating hazards, with a wide range of negative impacts on the economy, society and environment. As cylindrical shrubs and twigs are typical fuel loads in wildfires, it is important to understand how the diameter and arrangement of cylindrical fuels affect ignition behaviors. In this work, the piloted ignition of cylindrical wood rods with different diameters (3.2 15.9 mm) are conducted under the irradiation up to 50 kW/m2. Three fuel groups are tested: (I) single vertical rod, (II) single horizontal rod, and (III) horizontal rod bed attached to the ground. For a single vertical rod, the measured ignition time decreases as the diameter is decreased from 15.9 mm to 6.4 mm, showing a thermally-thin behavior. However, the ignition of the 3.2-mm rod is more difficult than the 9.5-mm rod, because of the enhanced convective cooling by the smaller curvature. Nevertheless, when the rod fuels are placed horizontally on the ground, the curvature-enhanced convective cooling becomes limited. For a single rod, when both the fuel diameter and the irradiation are small, only smoldering ignition occurs, and eventually the sample collapses. For the rod bed, flaming ignition always occurs, and it is easier to ignite because of a smaller convective cooling. For both horizontal configurations, the fuel ignition temperature increases almost linearly with the diameter from 270℃ (3.2 mm) to 330℃ (15.9 mm) but is insensitive to the irradiation level. This research quantifies the effect of fuel diameter and arrangement on the piloted ignition and reveals that the traditional classification of thermally thin and thick fuel for flat materials may not be suitable for cylindrical wildland fuels.